Effect of some chemical decontaminants on the survival of Listeria monocytogenes and Salmonella Typhimurium with different attachment times on chicken drumstick and breast meat - Ilhak, Osman Irfan; Incili, Gokhan Kursad; Durmusoglu, Halil (Springer India, 2018)
The aim of this study was to investigate the efficacy of some decontaminant agents on the survival of Salmonella Typhimurium and Listeria monocytogenes with different attachment periods to chicken drumstick with skin and skinless breast meat. For this purpose, S. Typhimurium and L. monocytogenes were given periods of 0.5 (30 s), 20 and 210 min to attach to the chicken drumstick and breast meat. At the end of the each attachment period, the meat samples were treated with lactic acid, (2 and 4%), cetylpyridinium chloride (0.5%) and acidified sodium chlorite (1200 ppm). In the drumstick sample treated with cetylpyridinium chloride, the reduction level of L. monocytogenes with 30 s attachment period was 3.2 log(10) CFU/ml while the reduction level was found to be 2.2 log(10) CFU/ml with 20 min attachment period. Decontamination with acidified sodium chlorite resulted in reduction of 1.8 log(10) CFU/ml in S. Typhimurium attached to the chicken drumstick for 30 s while the reduction levels of S. Typhimurium with 20 and 210 min attachment periods were 1.2 and 1.3 log(10) CFU/ml, respectively. The results indicated that some antimicrobial agents have more strong effect on L. monocytogenes and S. Typhimurium on the chicken meat parts in the first 30 s of attachment. However, there were no changes in the efficacy of the decontaminants on the survival of L. monocytogenes and S. Typhimurium on chicken meat when the attachment time of these bacteria were extended from 20 min to 210 min.
Keywords: Listeria monocytogenes; Salmonella Typhimurium; Attachment period; Chicken meat; Decontamination